PERCEPTION OF LECTURERS ON THE USE OF INFORMATION ANDCOMMUNICATION TECHNOLOGY FOR THE EFFECTIVE TEACHINGOF TECHNICAL EDUCATION PROGRAMME - Kennedy, O. O. (Sokoto Educational Review, 2019)
The study investigated the extent to which ICT has been used in the teaching o f technical education programme in tertiary’ institutions as well as the benefits to both staffs and students. Three research questions were posed to guide the study. The survey research design was adopted. The target population was 42 lecturers of technical education in tertiary institutions in South-South Nigeria comprising Delta State University Abraka, University of Benin, Benin City, Federal College of Education (Technical), Asaba, Umunze and Omoko. No sampling was done as the population was few. A questionnaire was developed, validated and its reliability established. Mean and standard deviation were used to answer the research questions. Results showed that the use of ICT was well entrenched and evidently of help in the teaching and learning of technical education programme in tertiary institutions in South-south Nigeria. Recommendations such as training and retraining of technical education staffs on ICT who have a part to play in improving technical education programmes were made among others.